2020
DOI: 10.1371/journal.pone.0232863
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation activates glial cells and inhibits neurogenesis after pneumococcal meningitis

Abstract: Pneumococcal meningitis (PM) causes damage to the hippocampus, a brain structure critically involved in learning and memory. Hippocampal injury-which compromises neurofunctional outcome-occurs as apoptosis of progenitor cells and immature neurons of the hippocampal dentate granule cell layer thereby impairing the regenerative capacity of the hippocampal stem cell niche. Repetitive transcranial magnetic stimulation (rTMS) harbours the potential to modulate the proliferative activity of this neuronal stem cell n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Considering their role in pathological brain states (Graeber and Streit, 2010; Prinz et al, 2019; Prinz et al, 2021), it is interesting to theorize that the therapeutic effects of rTMS could—at least in part—depend on the modulation of microglia function. Indeed, evidence has been provided that rTMS affects microglial markers (Clarke et al, 2017; Cullen and Young, 2016; Li et al, 2021; Muri et al, 2020; Stevanovic et al, 2019). However, direct experimental evidence determining the role of microglia in rTMS-induced neural plasticity is currently not available.…”
Section: Introductionmentioning
confidence: 99%
“…Considering their role in pathological brain states (Graeber and Streit, 2010; Prinz et al, 2019; Prinz et al, 2021), it is interesting to theorize that the therapeutic effects of rTMS could—at least in part—depend on the modulation of microglia function. Indeed, evidence has been provided that rTMS affects microglial markers (Clarke et al, 2017; Cullen and Young, 2016; Li et al, 2021; Muri et al, 2020; Stevanovic et al, 2019). However, direct experimental evidence determining the role of microglia in rTMS-induced neural plasticity is currently not available.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that 5-min daily cTBS (3 pulses of 50 Hz repeated every 200 ms, intensity at 200 G) applied on the infarcted hemisphere beginning at 3 h after photothrombotic stroke injury for continuous 5-day reduced M1 phenotype microglial activation and suppressed pro-inflammatory cytokines production [ 59 ]. In contrast, Lukas Muri et al reported that cTBS (three 30 Hz pulses repeated at intervals of 100 ms for 200 times) increased abundance of CD68 + cells (M1 phenotype) in cerebral cortex and hippocampal dentate gyrus [ 60 ]. Indeed, our present data set provided further evidence in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Considering their role in pathologic brain states (Graeber and Streit, 2010;Prinz et al, 2019Prinz et al, , 2021, it is interesting to theorize that the therapeutic effects of rTMS could, at least in part, depend on the modulation of microglia function. Indeed, evidence has been provided that rTMS affects microglial markers (Cullen and Young, 2016;Clarke et al, 2017;Stevanovic et al, 2019;Muri et al, 2020;Li et al, 2021). However, direct experimental evidence determining the role of microglia in rTMS-induced neural plasticity is currently not available.…”
Section: Introductionmentioning
confidence: 99%